2017
DOI: 10.3892/ol.2017.7041
|View full text |Cite
|
Sign up to set email alerts
|

miR‑20b promotes cellular proliferation and migration by directly regulating phosphatase and tensin homolog in prostate cancer

Abstract: Abstract. MicroRNAs are small non-coding RNAs, which are critical regulators of carcinogenesis and tumor progression. Previous studies have identified that microRNA-20b (miR-20b) acts as an oncogene in numerous cancers. However, the role of miR-20b in prostate cancer remains unclear. The present study aimed to investigate the expression of miR-20b in prostate cancer and to examine whether modulating miR-20b expression impacts prostate cancer cellular proliferation and migration. It was revealed that miR-20b wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 38 publications
3
29
0
Order By: Relevance
“…MiR-20b belongs to a cluster of highly similar miRNAs called the miR-17 family [22]. Deregulation of miR-20b has been determined in many different cancers [13][14][15][23][24][25][26]. Our results demonstrated that miR-20b is overexpressed in both AGS and MKN28 GC cell lines compared to healthy gastric tissue, which is consistent with previous studies [13,14,27,28].…”
Section: Discussionsupporting
confidence: 91%
“…MiR-20b belongs to a cluster of highly similar miRNAs called the miR-17 family [22]. Deregulation of miR-20b has been determined in many different cancers [13][14][15][23][24][25][26]. Our results demonstrated that miR-20b is overexpressed in both AGS and MKN28 GC cell lines compared to healthy gastric tissue, which is consistent with previous studies [13,14,27,28].…”
Section: Discussionsupporting
confidence: 91%
“…Among these 26 HCC-related RNA editing sites, the top three affected miRNAs were miR-17-3p, miR-20b-3p, and miR-593-3p (with 11, 7, and 7 target regulation changes induced by HCC-related editing sites, respectively ( Supplementary Table S5). Notably, miR-17-3p, miR-20b-3p, and miR-593-3p are widely involved in caner initiation and progression, including HCC (42)(43)(44)(45)(46). We observed that the expression levels of 163 RNA editing sites were correlated with the editing degree of corresponding genes, of which 10 were HCC-related editing sites.…”
Section: The Functional Consequence Of Rna Editing Sitesmentioning
confidence: 79%
“…In addition, PTEN is regulated by miRNAs in ovarian, colon and breast cancer, glioma and other malignant tumors (28)(29)(30)(31). Notably, miR-20b regulates proliferation and migration of prostate cancer cells by directly targeting PTEN (12). Chu et al (32) demonstrated that the expression of PTEN is inhibited by miR-205, which is why miR-205 promotes proliferation and invasion of ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…miR-20b belongs to the miR-106a-363 gene cluster, and together with the miR-17-92 and miR-106b-25 clusters, it forms the miR-17 gene (9), which is active in the oncogenesis of certain types of human tumor (10). Increased miR-20b expression has previously been associated with decreased survival rate in gastric cancer (11), promotion of proliferation and migration of prostate cancer cells (12), and proliferation and DNA synthesis of breast cancer cells (13). miR-20b expression is altered in hepatocellular carcinoma, although its activity has not yet been described.…”
Section: Introductionmentioning
confidence: 99%